Flipped classroom in the development of the communicative skills at “Emiliano Hinostroza High School” - Zhuño-Morocho, Jorge Patricio; Guamán-Luna, Martha Magdalena (IUSTITIA SOCIALIS, 2022)
The implementation of interactive strategies to develop oral skills and consolidate a model to improve English as a foreign language is lacking in rural schools. The main purpose of this research is to explore the effectiveness of the flipped classroom in the development of oral expression in 1st and 2nd year high school students of the rural school "Emilio Hinostroza" and to determine the likes and dislikes of the students for the activities, resources and results of the flipped classroom. For this purpose, a questionnaire with closed and open-ended questions was used to determine the students’ perceptions. The findings of the study provide information on some benefits with respect to student motivation and performance, and make the flipped classroom model a tool worthy of consideration for teaching English synchronously and asynchronously.